Clinical epidemiology of herpes zoster and postherpetic neuralgia in Barcelona (Spain). A single-center study - Salleras, Montserrat; Salvador, Patricia; Salleras, Lluís; Soldevila, Núria; Prat, Andreu; Garrido, Patricio; Domínguez, Angela (Frontiers in Public Health, 2026)
IntroductionVaricella-zoster virus is an alphaherpesvirus that causes two diseases in humans: chickenpox, the primary infection, and herpes zoster (HZ). Although HZ incidence has been well-documented, relatively little is known regarding the clinical-epidemiological characteristics of HZ prodromal pain, acute pain, and subacute pain. The aim of the study was to analyse the clinical-epidemiological characteristics of HZ and postherpetic neuralgia (PHN) in cases diagnosed between 2007 and 2020.MethodsWe conducted a clinical-epidemiological study of cases of HZ and PHN diagnosed between 2007 and 2020 in Hospital de Sagrado Corazón (Barcelona) in the first 14 days after rash onset, analyzing age, gender, dermatomes, and pain. Pain on rash diagnosis was classified as no pain, any pain, and clinically significant pain (scores 0, 1–10, and 3–10, respectively).ResultsA total of 589 cases of HZ were included, mean age of patients was 59.6 years and the female/male ratio was 1.38 and cases increased with age (p < 0.01). Of the 589 cases, 77.4% had pain on day 0 of rash onset, 34.5% at 30 days, and 11.9% at 90 days. 70 cases progressed to PHN, which also increased with age. Factors associated with PHN were age groups 70–79 years (aOR 4.26; 95% CI 1.36–13.37) and ≥80 years (aOR 3.89; 95% CI 1.18–12.87) and intensity of pain score at rash onset ≥7 (aOR 19.74; 95% CI 4.63–84.10).ConclusionsPatient age and pain presence and intensity on day 0 and at 30 days of HZ diagnosis are the main risk factors for PHN.